In Neotropical savannas, altitude affects the diversity of the Anisoptera but not the Zygoptera (Insecta: Odonata) (2020)
Lentic and lotic habitats, combined with varying altitudes, may have differential effects on communities of the Order Odonata. We sampled adult odonates at 94 waterbodies of the Orinoquía region of eastern Colombia. Our hypothesis was that species composition and richness, as well as abundance, would be affected by both altitude and habitat. Overall, 70 of the 100 species recorded in the study were sampled in both lotic and lentic environments, with 16 species (5 in the Suborder Zygoptera and 11 in the Suborder Anisoptera) occurring only in lentic habitats and 14 occurring exclusively in lotic habitats (13 Zygoptera, 1 Anisoptera). The results of the analysis indicated that the species richness and abundance of anisopterans were affected by altitude, whereas the diversity of zygopterans was not affected in any way. Despite these mixed findings, the results for anisopterans were consistent with the results of previous studies, which have indicated altitude as a primary determinant of the Odonata diversity through its effect on the dynamics of water flow and the shift from lentic to more lotic environments. Further studies over a more ample altitudinal gradient should provide more conclusive evidence, particularly regarding the role played by both altitude and habitat on the local diversity of odonates.